Numerical and experimental analysis of a side -polished single-mode fiber for refractive index sensing - Bilal, Muhammad Musavir; Thottoli, Ajmal; Grande, Marco; Lopez-Aguayo, Servando (Advanced Optical Technologies, 2025)
In this paper, we introduce a comprehensive study, based on both numerical and experimental analyses, of side polished-single mode fibers (SP-SMF) to investigate their corresponding evanescent field interaction with air and liquid analytes such as water and isopropanol (IPA). On the one hand, the SP-SMF’s optical properties are numerically studied and analyzed by using the finite element method and the beam propagation method, and we find that the alteration of analytes at the sensing region enhances the change in the refractive index (RI) of the materials. On the other hand, we designed and built an ad-hoc experimental setup to characterize the SP-SMF when air, water, and IPA are introduced into the SP region. The sensitivity is measured as 1.207 V/RIU. The performance in terms of effective RI and transmittance are reported to show how these SP-SMFs can be efficiently used for calculating the liquid RI. The simulation and experimental results display the significant performance of the SP-SMF as a valuable sensing element.